Prevalence of pharmacological adherence in patients with coronary artery disease and associated factors - Jaqueline Correia Padilha; Vinicius Batista Santos; Camila Takao Lopes; Juliana de Lima Lopes
Objective: to assess the prevalence of pharmacological adherence in patients with coronary artery disease and to identify factors associated with adherence. Method: a crosssectional, correlational study, including 198 patients with a previous diagnosis of coronary artery disease. Pharmacological adherence was assessed by the four-item Morisky Green test, and the factors that potentially interfere with adherence were considered independent variables. The association between the variables was determined by the Cox model, with a 5% significance level. Results: 43% of the patients adhered to the treatment. Fatigue and palpitation, never having consumed alcohol and being served by medical insurance were associated with adherence. Lack of adherence was associated with considering the treatment complex, consumption of alcohol and being served by the public health care system. In the multiple analysis, the patients with fatigue and palpitations had a prevalence of adherence around three times higher and alcohol consumption was associated with a 2.88 times greater chance of non-adherence. Conclusion: more than half of the patients were classified as non-adherent. Interventions can be directed to some factors associated with lack of adherence.